Leishmanicidal Compounds from the Fruits of Piper longum - Ghosal, Sabari; Deb, Anindita; Mishra, Priyanka; Vishwakarma, Ram (Planta Medica, 2012)
One new alkaloid amide, piperlongumide (1) [N-isobutyl-19-(3′,4′-methylenedioxyphenyl)-2E,4E nonadecadienamide], and six known compounds with leishmanicidal activity against promastigotes and axenic amastigotes of Leishmania donovani were isolated from the n-hexane fraction of the fruits of Piper longum. The structure of 1 was elucidated by spectroscopic evidences.
Keywords: Piper longum; Piperaceae; piperlongumide; Leishmania donovani; promastigotes; axenic amastigotes